2017
DOI: 10.6000/1927-5129.2017.13.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Okra Yellow Vein Mosaic Virus (OYVMV) on Plant Growth and Yield

Abstract: Okra yellow vein mosaic virus (OYVMV) is one of the most destructive diseases of okra plant. In the current study, effect of okra yellow vein mosaic virus (OYVMV) was assessed on plant growth and yield in naturally infected crop under agro-ecological conditions of Hyderabad district. The virus showed the significant reduction in plant height, number of leaves, flowers, fruits, and over all pickings and yield of all the locations wherever the crop was examined in the district. The significant reduction in plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Again results in this work showed percentage reduction was high in that Rafiki and Indiana but low in Essoumtem, indicating a possible tolerance to both virus and drought combination stress. This was in line with the findings of Khaskheli et al 22 , who reported a significant reduction in plant height of okra grown in four different locations and infected with the yellow vein mosaic virus as compared to healthy plants. Amiteye et al 23 also reported that plant height was significantly reduced in diseased plants of all ten okra cultivars infected with the okra mosaic virus (OkMV).…”
Section: Discussionsupporting
confidence: 93%
“…Again results in this work showed percentage reduction was high in that Rafiki and Indiana but low in Essoumtem, indicating a possible tolerance to both virus and drought combination stress. This was in line with the findings of Khaskheli et al 22 , who reported a significant reduction in plant height of okra grown in four different locations and infected with the yellow vein mosaic virus as compared to healthy plants. Amiteye et al 23 also reported that plant height was significantly reduced in diseased plants of all ten okra cultivars infected with the okra mosaic virus (OkMV).…”
Section: Discussionsupporting
confidence: 93%
“…The virus poses a serious threat to okra cultivation worldwide including in Sindh, Pakistan owing to its long-term survival in the insect vector, highly efficient transmission through the insect vector and overlap cropping. In the Hyderabad district, Sindh-Pakistan, the BYVMV significantly reduces all plant growth and yield parameters under natural infection conditions (Khaskheli et al, 2017). Kumbhar (2017) concluded from his survey study that OYVMD prevails in districts of Hyderabad, Tando Allahyar, Matiari, and Sanghar (Sindh-Pakistan) with high incidence and severity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in general, Zn and Cu-deficient plants are highly susceptible to plant diseases (Grewal et al 1996 in wheat andHelfenstein et al, 2015 in soybean) as these minerals protect plants against pest and disease infestations (Marschner, 1995). Khaskheli et al (2017) reported that the yellow vein mosaic virus significantly reduced plant height, number of leaves, flowers, fruits, and overall pickings and yield of okra. Most resistant genotypes were reported to be very poor in yield and fruit quality (Nizar et al 2004).…”
Section: Discussionmentioning
confidence: 99%